EVALUASI KONTRIBUSI PAJAK AIR TANAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN SIKKA - Carolina Yunyta Duminggu; Emilianus Eo Kutu Goo; Maria Silvana M. Carcia (Universitas Nusa Nipa Maumere, 2026)
Abstract. Locally Generated Revenue (PAD) is an important indicator in assessing a region's fiscal independence. One source of PAD with potential for development is Groundwater Tax (PAT), particularly in areas with significant groundwater utilization. This study aims to evaluate the contribution of Groundwater Tax to Locally Generated Revenue (PAD) in Sikka Regency during the 2020–2024 period. The research method used is descriptive with quantitative and qualitative approaches. The data used are secondary data obtained from the Sikka Regency Regional Revenue Agency, including data on realized Groundwater Tax and PAD revenues, as well as primary data obtained through observations and interviews during the internship. Data analysis techniques were used to calculate the contribution of Groundwater Tax to.Total PAD and analyze its revenue development from year to year. The results show that the contribution of Groundwater Tax to Sikka Regency's PAD is still relatively small and fluctuates, although overall PAD realization is quite effective. This low contribution is influenced by several factors, including suboptimal taxpayer compliance, limited human resources, and the suboptimal implementation of the regional tax digitalization system. Therefore, strategic efforts are needed in the form of increasing supervision, taxpayer data collection, tax socialization, and optimization of the tax administration system to increase the contribution of Groundwater Tax to Sikka Regency's PAD in the future